'Infinite use of finite means': the creative aspect of the lexicon of English as seen through some samples of engineering jargon / Yuthandy Maniam - Yuthandy Maniam (Universiti Teknologi MARA, Sarawak, 2004)
This article is a simple study of the creative aspect of language, aptly described as 'the infinite use of finite means' by Wilhelm von Humboldt (Brown 1967: 82). More specifically it aims to demonstrate that the lexicon of the English Language (like any other language, for that matter) is self-generative. This is done by examining the formal and semantic relations between some samples of Engineering jargon, on the one hand, and the vocabulary of common ordinary usage including word formative lexical elements in the language, on the other, in order to show that the former is created from the latter ('more or less strained or extended use of old linguistic material' - (Sapir 1921: 17). The introduction explains the focus of the study in greater detail and also introduces certain notions and concepts used in the analyses that follow in the two major sections of the article. Section 1 examines the nature of the formal relations between the jargon and the lexical material from which it is created. Section 2 goes a step further to analyze the nature of the semantic relations underlying the formal relations described in Section 1. It is hoped that the analyses undertaken in both these sections will successfully show that the Engineering jargon is truly the result of the creative process operating within the lexicon of the language.